A termografia infravermelha como ferramenta para o monitoramento da dor muscular de início tardio, dano muscular e recuperação no esporte - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The practice of physical exercise is an essential ally for maintaining health and quality of life. In this context, so that gains can be obtained in terms of performance and recreational level, the monitoring and control of training loads are essential to maximizing its gains. On the other hand, exercise without adequate planning can induce exercise-induced muscle damage and delayed onset muscle soreness (DOMS). DOMS is accomplished by several symptoms, such as strength loss, loss of range of motion, and local pain. As a result, it is interesting for coaches, athletes, and physiotherapists to understand better how to quantify this situation to limit its symptoms. Currently, different approaches have been explored to monitor muscle damage and DOMS. However, many of them are invasive, do not provide immediate feedback, also expensive, such as the quantification of blood markers. At the other extreme, we have behavioral measures that have a subjective character. Infrared thermography (IRT) appears as a possible alternative to monitor post-exercise recovery under the justification that changes in skin temperature is correlated with the inflammation process potentialized by muscle damage and DOMS. With the combination of experiments carried out over four years, the central objective of this Ph.D. thesis was to investigate whether the skin temperature, evaluated by IRT, under resting conditions and after the practice of the physical exercise, can be used to monitor exercise-induced muscle damage and DOMS in post-exercise recovery. Our main results indicated that: (1) When analyzes of thermal imagens are performed by evaluators with different levels of experience, the mean and maximum temperature should be prioritized due to better reproducibility, (2) Changes in skin temperature induced by exercise show a sex-dependent effect, (3) Changes in skin temperature after exercise did not relate to DOMS, but there was a positive relationship between maximum skin temperature and pressure pain threshold in the variation between pre-exercise and 48 h postexercise, (4) Exercise-induced muscle damage did not reflect in changes in skin temperature rewarming after cold stress test applied 48h post-exercise. We consider that information in this thesis contributes to the formation of knowledge in the area; with an integrative approach of concepts and experiments, we sought to understand better IRT's applicability to monitoring exercise-induced muscle damage, DOMS, and recovery status after physical exercise.
Infrared thermography as a tool for monitoring delayed onset muscle soreness, muscle damage, and recovery in sports
Keywords: Termografia; Exercício físico; Dano muscular; Recuperação pós-exercício; Thermography; Physical exercise; Muscle damage; Post-exercise recovery; CNPQ::CIENCIAS DA SAUDE